Migration and informal insurance - Costas Meghir; Ahmed Mushfiq Mobarak; Corina Mommaerts; Melanie Morten (Yale University, Economic Growth Center, 2019)
Do new migration opportunities for rural households change the nature and extent of informal risk sharing? We experimentally document that randomly offering poor rural households subsidies to migrate leads to a 40% improvement in risk sharing in their villages. We explain this finding using a model of endogenous migration and risk sharing. When migration is risky, the network can facilitate migration by insuring that risk, which in turn crowds-in risk sharing when new migration opportunities arise. We estimate the model and find that welfare gains from migration subsidies are 42% larger, compared with the welfare gains without spillovers, once we account for the changes in risk sharing. Our analysis illustrates that (a) ignoring the spillover effects on the network gives an incomplete picture of the welfare effects of migration, and (b) informal risk sharing may be an essential determinant of the takeup of new income-generating technologies.
More recent version: http://hdl.handle.net/10419/243242
Keywords: D12; D91; D52; O12; R23; 330; Informal Insurance; Migration; Bangladesh; RCT